The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1159/000217970
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of SCC Antigen in the Serum of Patients with Head and Neck Cancer

Abstract: SCC antigen (Ag) is a tumor-associated Ag (TAA) obtained from squamous cell carcinoma of the uterine cervix. This study reports the evaluation of this TAA in patients with head and neck malignant diseases and its possible prognostic value. Serum samples from 28 patients with benign head and neck diseases from 399 patients with cancer were obtained prior to treatment. SCC Ag serum levels were determined by radioim-munoassay using 2.5 ng/ml as the upper limit of normality. Elevated SCC Ag serum levels were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 6 publications
1
22
0
3
Order By: Relevance
“…SCC antigen was originally discovered as a tumor marker for cervical cancer [32], and was shown to be a prognostic factor for both cervical and head and neck cancer [33, 34]. In the case of esophageal cancer, 25–28.6% of the patients with SCC are SCC antigen positive [28, 29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…SCC antigen was originally discovered as a tumor marker for cervical cancer [32], and was shown to be a prognostic factor for both cervical and head and neck cancer [33, 34]. In the case of esophageal cancer, 25–28.6% of the patients with SCC are SCC antigen positive [28, 29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…No correlation was evident between serum SCC Ag levels and age, or nodal metastases. In patients with primary tumors, SCC Ag levels were associated with nodal involvement and tumor location, with significantly higher levels in tumors of the nasopharynx and piriform sinus [29]. Lara and Cuyas [28] indicated for laryngeal cancer an elevated sensitivity (68%), significantly related to T, N and M stage.…”
Section: Head and Neck Cancermentioning
confidence: 97%
“…0.002) [29]. SCC Ag is an excellent marker of residual disease after primary treatment that can lead to the addition of other therapeutic procedures, when high elevated treatment SCC Ag levels indicated incomplete surgical resection (p !…”
Section: Head and Neck Cancermentioning
confidence: 99%
“…However, the neutral form encoded by the SCCA1 gene is found in normal and some malignant cells [5]. Clinical studies have shown that SCC is elevated in the sera of 34-59% of untreated patients [6,7] predominantly at late stages or with large tumour size [1,3,4]. A correlation between serum levels of SCC and invasion of cervical nodes was found in two studies [1,3].…”
Section: Introductionmentioning
confidence: 99%